11 Validation of the FAST-ED score for prehospital identification of stroke patients with large-vessel occlusion and a comparison with the clinician's judgment. (26th April 2019) - Puolakka, T; Virtanen, P; Kuisma, M; Strbian, D
Abstract : Background: Endovascular thrombectomy (EVT) is a highly effective treatment for acute ischemic stroke patients with large-vessel occlusion (LVO). However, few comprehensive stroke centers are capable of providing EVT 24/7 and their geographical position is not necessarily ideal. We aimed to validate FAST-ED scale as a tool for LVO identification and hospital selection in the field and to compare it with the clinician's judgment. Method: All thrombolysis candidates transported by the emergency medical services from January to June 2017 were evaluated for FAST-ED scale items by two investigators (TP, DS). A neuroradiologist (PV) evaluated the presence of vessel occlusion on the admission CT angiography in a blinded manner. To compare two independent raters (TP, DS), interclass correlation coefficient was calculated based on a sub-cohort of 100 patients. Results: The sample consisted of 610 thrombolysis candidates. LVO was diagnosed in 39 cases (6.4%). Majority of the patients (81.8%) scored 0–3 on FAST-ED scale. Sensitivity of FAST-ED ≥4 to predict LVO was 58%, whereas the specificity 87% and the negative predictive value 94%. For more experienced clinician, it was 79.4%, 88% and 97%, respectively. For less experienced clinician the corresponding numbers were 50%, 89%, and 92%. Interclass correlation coefficient for both raters for the whole range of FAST-ED was 0.92 (0.88–0.94). Conclusion: The higher the FAST-ED score, the higher the probability of correctly identifying LVO in the field. However, with the most commonly used cut-off of ≥4 points, only 28% of the thrombolysis candidates had LVO. Reference: Lima FO, Silva GS, Furie KL, Frankel MR, Lev MH, Camargo ÉC, et al . Field assessment stroke triage for emergency destination: A Simple and Accurate Prehospital Scale to detect large vessel occlusion strokes. Stroke 2016;47:1997–2002. Conflict of interest: None. Funding: Helsinki University Hospital EVO, Etelä-Karjalan Lääkäriseura and Viipurin Duodecim, Viipurin tuberkuloosisäätiö.